Clinical performance evaluation of the Idylla NRAS-BRAF mutation test on retrospectively collected formalin-fixed paraffin-embedded colorectal cancer tissue. Issue 4 (12th September 2017) - Johnston, Louise; Power, Michael; Sloan, Philip; Long, Anna; Silmon, Angela; Chaffey, Ben; Lisgo, Andrea Jane; Little, Liam; Vercauteren, Ellen; Steiniche, Torben; Meyer, Tine; Simpson, John
Abstract : Aims: Understanding the molecular mechanisms of underlying disease has led to a movement away from the one-drug-fits-all paradigm towards treatment tailored to the genetic profile of the patient. The Biocartis Idylla platform is a novel fully automated, real-time PCR–based in vitro diagnostic system. The Idylla NRAS-BRAF mutation test has been developed for the qualitative detection of mutations in NRAS and BRAF oncogenes, facilitating genetic profiling of patients with cancer. The aim of this study was to carry out a formal clinical performance evaluation. Methods: Two-hundred and forty-two formalin-fixed paraffin-embedded (FFPE) human malignant colorectal cancer (CRC) tissue samples were identified in departmental archives and tested with both the Idylla NRAS-BRAF mutation test and the Agena Bioscience MassARRAY test. Results: The overall concordance between the Idylla NRAS-BRAF mutation test and the MassARRAY comparator reference test result was 241/242 (99.59%, lower bound of one-sided 95% CI=98.1%) for NRAS and 242/242 (lower bound of 95% one-sided 95% CI=98.89%) for BRAF . The Idylla NRAS-BRAF test detected one NRAS mutation that had not been reported by the MassARRAY comparator reference test. Reanalysis of this sample by droplet digital PCR confirmed that the mutation was present, but at an allelic frequency below the stated sensitivity level of the MassARRAY system. Conclusion: These results confirm that the Idylla NRAS-BRAF mutation test has high concordance with a widely used NRAS-BRAF test, and is therefore suitable for use as an in vitro diagnostic device for this application.